Study the Optimal Operative Conditions of New Glow Discharge Ion Source for Polymeric Treatment. Issue 1 (1st August 2022) - Hassan, M.G.; Soliman, B.A.; El-Saftawy, A.A.; Abdelrahman, M.M.; Abdelmageed, K.E.; Hassouba, M.A.
Abstract: The design, manufacturing, and systematic parametric evaluation of a modified glow discharge ion source (with a pear-shaped anode and a plane cathode) are detailed to extract low-power, high plasma density, and high-intensity ion beam current for material processing. The study includes determining the optimal operative conditions for ion source performance and optimizing its properties. The ion beam current was measured at various argon gas pressures and anode-cathode distances as well as its measurements at various ion source - collector plate distances. At the optimum settings, the influence of discharge pressure on the output current was evaluated using various gases (argon, oxygen, nitrogen and hydrogen). In addition, the influence of applied negative voltages on the extractor electrode (different hole diameters) on the generated ion beam current is being explored. Finally, SIMION computer program evaluated and studied ion beam optics. The simulation and experimental results for a highly efficient ion beam derived from the planned ion source agreed well.